Smart logbook sebagai alternatif penyelesaian masalah penyeliaan berterusan latihan industri: kajian awal persepsi pelajar (Smart logbook as alternative solution for continouos industrial training supervision problem: a purview study on student's perception) / Sulaiman Mahzan ...[et al.] - Mahzan, Sulaiman; Nurr Sadikan, Siti Fairuz; Md Shah, Mohd Ab Malek; Shahudin, Mohd Harun; Saat, Zaini; Shafie, Shamsol (Universiti Teknologi MARA, 2020)
Supervision and monitoring of practical students are among the pertinent components in the a costs, wastes supervision time for travel and stresses other factors in managing industry supervision such as ongoing supervision, verification of customization of industry entities regarding needs and reduction of allocation by IPT. Thus, a new mechanism needs to be implemented by considering the advantages and benefits that can be developed throughout the use of information technology (IT). In conjunction with this circumstance, a Smart LogBook prototype has been developed to address the problems encountered in the supervision process of the industry training students as stated. A study of students' perceptions of the Smart Log book prototype was also tailored to assess student perception compared to using supervisory methods using the old logbook. The Rapid Application Development (RAD) methodology was used in software development while a set of questionnaires was distributed to 65 respondents to obtain their assessment feedback data. The findings show that students have a positive assessment of their perception of the use of this prototype.